2010
DOI: 10.1002/ajmg.a.33344
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation in eight new patients with a deletion encompassing 2q31.1

Abstract: Microdeletions of the 2q31.1 region are rare. We present the clinical and molecular findings of eight previously unreported patients with overlapping deletions in 2q31.1. The patients have a variable clinical phenotype and present with developmental delay (7/8), growth retardation (5/8), seizures (2/8) and a craniofacial dysmorphism consisting of microcephaly (4/8), short palpebral fissures (7/8), broad eyebrows with lateral flare (7/8), low-set ears with thickened helices and lobules (5/8), and micrognathia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 49 publications
2
26
3
1
Order By: Relevance
“…This locus was identified from reports of cytogenetically visible deletions involving 2q31 in patients with syndromal SHFM. Variable limb anomalies, including SHFM, have been described in association with a number of other findings, such as growth delay, developmental disability, microcephaly, cleft palate, craniofacial dysmorphism, seizures, and anomalies of the brain, eyes, heart, and genitalia [Benson et al, 1986;Ramer et al, 1990;Boles et al, 1995;Nixon et al, 1997;Del Campo et al, 1999;Goodman et al, 2002;Pescucci et al, 2007;Svensson et al, 2007;Davidsson et al, 2008;Tsai et al, 2009;Mitter et al, 2010;Dimitrov et al, 2011;Theisen et al, 2011]. The deletions associated with SHFM have varied in size, and most have been sporadic, but some familial cases have been described [Ramer et al, 1990;Del Campo et al, 1999].…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This locus was identified from reports of cytogenetically visible deletions involving 2q31 in patients with syndromal SHFM. Variable limb anomalies, including SHFM, have been described in association with a number of other findings, such as growth delay, developmental disability, microcephaly, cleft palate, craniofacial dysmorphism, seizures, and anomalies of the brain, eyes, heart, and genitalia [Benson et al, 1986;Ramer et al, 1990;Boles et al, 1995;Nixon et al, 1997;Del Campo et al, 1999;Goodman et al, 2002;Pescucci et al, 2007;Svensson et al, 2007;Davidsson et al, 2008;Tsai et al, 2009;Mitter et al, 2010;Dimitrov et al, 2011;Theisen et al, 2011]. The deletions associated with SHFM have varied in size, and most have been sporadic, but some familial cases have been described [Ramer et al, 1990;Del Campo et al, 1999].…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%
“…Notably, balanced chromosome rearrangements at 2q31.1, located either cetromeric or telomeric to the HOXD cluster, have been identified in several patients with limb malformations, including long bone deficiencies and digital absence [Dlugaszewska et al, 2006]. With the advent of array CGH, a number of additional deletions involving 2q31.1 have been identified and characterized, and attempts have been made to localize the regions responsible for different phenotypic features, including limb anomalies [Pescucci et al, 2007;Svensson et al, 2007;Davidsson et al, 2008;Tsai et al, 2009;Mitter et al, 2010;Dmitrov et al, 2011;Theisen et al, 2011]. Although it has also been hypothesized that deletion of the DLX1 and DLX2 genes, which reside centromeric to EVX2 and the HOXD cluster, may cause SHFM and other limb anomalies, this was not supported in two recent reports, and it appears that deletions excluding the HOXD cluster and its regulatory regions are not sufficient to cause limb anomalies [Dimitrov et al, 2011;Theisen et al, 2011].…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%
“…For example, the 2q31 microdeletion syndrome is caused by different deletions of various sizes, overlapping with the LNP-ATP5G3 gene desert on the centromeric side of the HOXD cluster. This syndrome is associated with hand malformations resembling mutations into the HOXD13 gene, even in patients where the HOXD gene cluster itself is not deleted (16), suggesting that such deletions affect regulatory elements controlling HOXD gene expression in developing limbs rather than the genes themselves.…”
mentioning
confidence: 99%
“…A genome wide linkage meta-analysis mapped 19q13.42, (the location of the NLRP2-Glu292Asp mutation in the current study) to patients with genetic generalized epilepsy in 379 families [27]. Five studies reported 2q31.1 deletions in patients with seizure related phenotypes including a migrating partial seizure of infancy [28] and two patients with develop delay and seizure [29]. More than 30 children with 2q interstitial deletion have been reported (for review, please see [30]).…”
Section: Discussionmentioning
confidence: 96%